The function y = f ( x ) satisfies the following:
4 x d x 2 d 2 y + 4 x ( d x d y ) 2 + 2 d x d y − 1 = 0
It is further given that x = t 2 and y = ln ( v ) . What is d t 2 d 2 v ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
d t d v = d y d v d x d y d t d x
Note that:
y = l n ( v ) ⇔ v = e y ⇔ d y d v = e y = v
f ′ = d x d y ; d t d x = 2 t
Putting those together:
⇒ d t d v = v f ′ ( 2 t )
⇒ d t 2 d 2 v = d t d ( v f ′ ( 2 t ) ) = d t d v f ′ ( 2 t ) + v d t d f ′ ( 2 t ) + v f ′ d t d ( 2 t )
⇒ d t 2 d 2 v = v ( f ′ . 2 t ) 2 + v f ′ ′ ( 2 t ) 2 + 2 v f ′ = 2 v ( 2 t 2 f ′ 2 + 2 t 2 f ′ ′ + f ′ )
Now come back to the given equation:
4 x d x 2 d 2 y + 4 x ( d x d y ) 2 + 2 d x d y − 1 = 0 ⇔ 4 t 2 f ′ ′ + 4 t 2 f ′ 2 + 2 f ′ = 1 ⇔ 2 t 2 f ′ 2 + 2 t 2 f ′ ′ + f ′ = 2 1
Hence: d t 2 d 2 v = 2 v ( 2 1 ) = v
Problem Loading...
Note Loading...
Set Loading...
Given that x = t 2 and y = ln v :
d x d y d x 2 d 2 y = d v d y × d t d v × d x d t = v 1 × d t d v × 2 t 1 = 2 v t 1 ( d t d v ) = d t d ( 2 v t 1 ( d t d v ) ) d x d t = 4 t 1 ( ( − v 2 t 1 ( d t d v ) − v t 2 1 ) d t d v + v t 1 ( d t 2 d 2 v ) ) = 4 x v 1 ( d t 2 d 2 v ) − 4 x v 2 1 ( d t d v ) 2 − 4 x v t 1 ( d t d v )
Therefore,
4 x d x 2 d 2 y + 4 x ( d x d y ) 2 + 2 d x d y − 1 v 1 ( d t 2 d 2 v ) − v 2 1 ( d t d v ) 2 − v t 1 ( d t d v ) + 4 x ( 2 v t 1 ( d t d v ) ) 2 + 2 v t 2 ( d t d v ) v 1 ( d t 2 d 2 v ) ⟹ d t 2 d 2 v = 0 = 1 = 1 = v